Correlation of Serum Vitamin D Levels in Young Myopes - Rukhsana Kousar; Sonika Syal; Hans Raj Sharma; Malvika Sharma; Riya Gupta; Manpreet Kaur (JK Science)
Background: Globally, myopia is a serious public health issue, and in recent years, its prevalence has been rising rapidly particularly in urban Asia. Aims: To determine the levels of serum vitamin D in young myopes and to find its correlation with myopia. Material and Methods: This was an hospital-based, cross sectional, observational study conducted in the Upgraded Department of Ophthalmology, Government Medical College Hospital, Jammu over a period of 6 months and included 56 patients with myopia and 56 patients as controls. All the myopic patients (n=56) underwent ophthalmologic examinations together with post cycloplegic refraction. Vitamin D levels of both the groups were measured. Data was then collected and analysed. Results: The mean age of myopes and controls were 17.20 ± 9.5 and 15.65 ± 8.9 years respectively. In the myopic group (n=56), 28.5 % had pre myopia, 39.2% had low myopia and 32.1% had high myopia. The mean serum vitamin D levels were 14.86 ± 7.64 ng/ml in myopic group and 26.03 ± 8.71 ng/ml in controls which was found to be statistically significant (p<0.01). There was a significant association between low serum vitamin D levels and myopia (p= 0.0002). In pre myopia patients we found out that 18.7% patients were having vitamin D deficiency while in patients with low myopia and high myopia the vitamin D deficiency was present in 45.4% and 61.1% respectively. Conclusion: In our study we found a significant association between low serum vitamin D levels and myopia (p= 0.0002). These findings suggest a potential association between myopia and vitamin D deficiency. In order to implement the role of vitamin D supplementation in young myopes, further longitudinal research must be conducted.